2011
DOI: 10.3174/ajnr.a2775
|View full text |Cite
|
Sign up to set email alerts
|

Post–Vertebral Augmentation Back Pain: Evaluation and Management

Abstract: BACKGROUND AND PURPOSE:Vertebral augmentation is an established treatment for painful osteoporotic vertebral fractures of the spine. Nevertheless, patients may continue to have significant back pain afterward. The purpose of this study was to assess the source of persistent or recurrent back pain following vertebral augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The lower lumbar spine, defined as the spine from the upper endplate of the fourth lumbar vertebra to the sacrum, is the most important part for determining lumbar lordosis. 38 , 39 In addition, it is the most common surgical site in degenerative spinal diseases. 40 The good outcome group had more lower lumbar lordosis with a cut-off point of 29°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower lumbar spine, defined as the spine from the upper endplate of the fourth lumbar vertebra to the sacrum, is the most important part for determining lumbar lordosis. 38 , 39 In addition, it is the most common surgical site in degenerative spinal diseases. 40 The good outcome group had more lower lumbar lordosis with a cut-off point of 29°.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the predictive factors for subsequent facet joint pain after a compression fracture, and the pain is associated with recurrent pain after a compression fracture and PV. 39–42 A literature review revealed different results in pain relief after facet joint injection. In our study, 16 of 31 patients underwent vertebroplasty, and only three patients had facet joint pain at the compression sites.…”
Section: Discussionmentioning
confidence: 99%
“…Dual or triple array epidural leads have been used to provide stronger axial coverage [ 19 , 20 ]. This may be important in patients with more diffuse lumbar pain associated with multiple vertebral compression fractures [ 11 - 13 ]. Another option is a combination of an epidural lead with a second lead positioned in the lumbar subcutaneous tissue for peripheral nerve field stimulation (PNFS) [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord stimulation or peripheral nerve field stimulation has been used to treat chronic pain after joint replacement [ 10 ]. Some degree of persistent pain after vertebral augmentation and kyphoplasties is common especially when the fractures are in the lumbar spine [ 11 , 12 ]. Back pain persisting after the first three months post vertebroplasty is seen in 19% to 23% of cases [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation